SOME DATA ABOUT MINERAL COMPOSION OF FINE GRAIN-SIZE FRACTION OF TIDAL MARSH SEDIMENTS IN DAY ESTUARY, NAM DINH PROVINCE - Hai, Luu Duc; Anh, Luong Duc; Dung, Luu Duc (Vietnam Journal of Marine Science and Technology, 2007)
The article presents the mineral composition of tidal marsh sediments in Day estuary by using X-Ray Analysis and Diferencial Thermal Analysis (DTA). The analyzed results show that: (1) the mineral  composition of fine grain-size fraction of the sediments consist mainly of clay minerals such as Glauconite,  Illite, Clorite, Monmorilonite, Kaolinite and Quartz; (2) the mineral composition of fine grain-size fraction  of the sediments clearly changes in spacial (sampling sites), but not dependents on the depth of sample column.